New or little-known Neotropical Dolichopodidae (Diptera) (II): genus Hercostomus Loew excluded from the Neotropics - Soares, Matheus M. M.; Capellari, Renato S.; Ale-Rocha, Rosaly (Zootaxa, 2023)
The Neotropical species of Hercostomus Loew are revised and the following new combinations are proposed: Paraclius panamensis (Van Duzee, 1931) comb. nov. (Panama), P. plumitarsis (Parent, 1931) comb. nov. (Bolivia), P. problematicus (Parent, 1930) comb. nov. (Brazil and Guyana) and Tachytrechus flavimanus (Van Duzee, 1934) comb. nov. (Brazil, Ecuador and Guyana). The type of Hercostomus petulans Parent, 1939 is lost, the species cannot be confidently identified and is here treated as a nomen dubium. As a result, the genus Hercostomus is formally excluded from the Neotropical Region. Paraclius problematicus comb. nov., P. latipes (Aldrich) and Tachytrechus flavimanus comb. nov. are redescribed based on additional material and photographs of type specimens. In addition, Paraclius maculipennis (Van Duzee, 1934) is regarded as a junior synonym of P. problematicus comb. nov. A new species of Paraclius from Costa Rica, P. norrbomi sp. nov. is described in the newly proposed latipes-group, along with P. aberrans Robinson, P. latipes and P. panamensis comb. nov.